An efficient coupling system using a thermophotovoltaic cell to harvest the waste heat from a reforming solid oxide fuel cell. (6th July 2017) - Dong, Qingchun; Cai, Ling; Liao, Tianjun; Zhou, Yinghui; Chen, Jincan
Abstract: The coupling system proposed here is composed of a reforming solid oxide fuel cell (R-SOFC) and a thermophotovoltaic cell (TPVC), where the synthesis gases (CH4 and CO) replacing H2 is used as fuel. The performance characteristics of the coupling system and R-SOFC are evaluated and compared. The optimal regions of the coupling system are determined and the parametric selection criteria are provided. The maximum power output densities of the R-SOFC-TPVC and SOFC-TPVC systems operated at 973–1273 K are calculated and compared with those of other SOFC-based coupling systems. It is found that the SOFC-TPVC or R-SOFC-TPVC system has some obvious advantages. Highlights: The proposed system consists of a reforming SOFC and a thermophotovoltaic cell. The maximum power density of the system is compared with that of a reforming SOFC. The optimal selective criteria of key parameters are provided. The system can efficiently harvest the waste heat from a reforming SOFC. The present system is revealed to have advantages over other SOFC-based systems.